Entropy change of a liquid system under the influence of radiation emission - Bulavin, L. A.; Gavryushenko, D. A.; Taradiy, K. V. (Reports of the National Academy of Sciences of Ukraine, 2016)
The influence of radiation emission on the structure features of liquid systems is studied by means of the fundamental Bogolyubov chain of equations for the case of stationary state. The non-equilibrium state of the liquid under the influence of radiation is regarded as the excitation of the equilibrium state. The dynamical representations which allow one to evaluate the entropy change due to the radiation emission influence are obtained. Since the mentioned non-equilibrium state is characterized by the pertubed distribution over momenta, the system of integro-differential equations for the evaluation of the pair distribution function is obtained.